Efecto de la combinación de sales (calcio, fósforo, hierro) en la osmolalidad de una bebida energizante a base de pitahaya amarilla (Selenicereus megalanthus). - Jiménez Ronquillo, Jehira Jocenzka (2023)
This research project is based on osmolality evaluation effect through mixture of mineral salts (calcium, iron, and phosphorus) to developme an energy drink made from a yellow pitahaya (Selenicereus megalanthus). The formulation of the energy drink follows Colombian Technical Standard 3837 for hydrating and energizing drinks for physical activity, exercise, and sports. This standard specifies concentration ranges of salts and required sugars to recover lost electrolytes during physical activity to fulfill osmolality limits greater than 340 mOsm/kg for energy drinks. On the other hand, Design Expert 8.0.7.1 software was used to create various formulations considering different factors. Factor A represents pitahaya pulp, factor B stands for water, factor C represents additives, factor D represents iron sulfate, factor E represents calcium lactate, and factor F represents calcium phosphate. The added salts were varied whilst factors A, B, and C remained constant. Sixteen treatments were generated, each subjected to two replications, for osmolality measurement. Physical and chemical analyses were performed on each sample, evaluating total soluble solids (ºBx), acidity index, pH, density, in accordance with Ecuadorian Technical Standard INEN 2304 for Soft Drinks or Non-carbonated drinks. Subsequently, the best treatment with optimal osmolality formulation was determined using Design Expert. Treatment T4 was identified as the most suitable, consisting of 81,01 % pitahaya pulp, 18,00 % water, 0,40 % additives, 0,01 % iron sulfate, 0,13 % calcium lactate, and 0,44 % calcium phosphate, resulting in an osmolality of 504 mOsm/kg, falling within the range of energy drinks. The drink was subjected to bromatological analyses, yielding the following data: 94,32 % moisture, 0,21 % ash, and 0,00 % fat. Nutritional analysis results include: 0,09 mg of iron, 0,00 % fiber, 0,02 mg of vitamin B2, < 0,08 mg of vitamin C, 0,08 % protein, 2,03 % sugars, < 0,01 mg of vitamin B3, 0,09 mg of calcium, and 5,47 % carbohydrates. The drink meets the maximum consumption level limits according to Ecuadorian Technical Standard INEN 2411 and NTC 3837 for Energy Drinks. Microbiological analyses resulted in < 10 CFU/ml of total coliform count, < 10 CFU/ml of mold count, <10 CFU/ml of total aerobic count, and < 10 CFU/ml of yeast count, meeting acceptance limits set by Ecuadorian Technical Standard INEN 2411-1 for Energy Drinks. Finally, a sensory analysis was conducted on yellow pitahaya-based energy drink, with a product acceptability rating of 89 %.